2021
DOI: 10.1016/j.jmig.2020.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Total Laparoscopic Hysterectomy of a 7400 g Uterus

Abstract: To demonstrate improved techniques and safety measures for total laparoscopic hysterectomy for a severely enlarged uterus. Design: Technical video of the surgery, which demonstrates various techniques for improved visualization, hemostasis, and manipulation for total laparoscopic hysterectomy for a 7400 g uterus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The first study on the ExCITE technique was conducted by Cesta et al [ 21 ] that reported a case of a woman who underwent laparoscopic total hysterectomy (with a uterus weighing 7400 g), bilateral salpingectomy and right ovariectomy. Following the ExCITE technique, the umbilical incision was enlarged up to 4 cm, and the surgical specimens were extracted using morcellation with a surgical scalpel.…”
Section: Discussionmentioning
confidence: 99%
“…The first study on the ExCITE technique was conducted by Cesta et al [ 21 ] that reported a case of a woman who underwent laparoscopic total hysterectomy (with a uterus weighing 7400 g), bilateral salpingectomy and right ovariectomy. Following the ExCITE technique, the umbilical incision was enlarged up to 4 cm, and the surgical specimens were extracted using morcellation with a surgical scalpel.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies tested the use of in-bag contained extracorporeal manual morcellation for large uteri after TLH, with the largest specimen weighing 1930 g[ 20 , 28 ]. In case of very large specimen, mostly single case reports, educational video articles and retrospective series with different technique and investigational devices have been reported[ 13 , 29 , 30 ]. To address these concerns, we developed an additional alternative technique of extracorporeal intrauterine morcellation carried out within the uterus utilizing its outer wall as a bag.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal and abdominal hysterectomy has been complemented by laparoscopic procedures, such as vaginal hysterectomy assisted by laparoscopy, laparoscopic subtotal and total hysterectomy, and robotic hysterectomy. The implementation of new techniques was related to "new" complications, a series of studies comparing the alternative approaches for hysterectomy and an ongoing craftsmanship among gynecological surgeons about what is possible in laparoscopic surgery [1] [2] [3]. At the same time, a contrary movement dedicated to the preservation of the uterus emerged [4] [5] [6].…”
mentioning
confidence: 99%